Characteristics and Real-World Outcomes of Patients Treated with Fecal Microbiota, Live-jslm (RBL) for the Prevention of Recurrent Clostridioides difficile Infection - Sahil Khanna; Sanghyuk Seo; Min Yang; Viviana Garcia-Horton; Yipeng Gao; Hannah H. Kim; Loren Ormenaj; Amy Guo (Infectious Diseases and Therapy)
Abstract Introduction Recurrent Clostridioides difficile infection (rCDI) is common, with symptoms ranging from diarrhea to life-threatening sepsis. This study aimed to assess the real-world outcomes of patients with rCDI in the United States (US) who received fecal microbiota, live-jslm (RBL), the first US Food and Drug Administration-approved microbiota-based therapy for the prevention of rCDI after antibiotic treatment. Methods Adults with rCDI who received RBL between July 2023 and August 2024 at home or in a clinic and had ≥ 8 weeks of follow-up or experienced CDI recurrence at any time after RBL administration were included. Treatment success, defined as no CDI recurrence within 8 weeks of RBL, was assessed overall and in subgroups stratified by age, number of prior CDI recurrences, duration of the antibiotic washout period, prior bezlotoxumab use, and RBL administration setting. Results Among 196 patients who received RBL, 176 had either ≥ 8 weeks of follow-up or had < 8 weeks of follow-up but experienced CDI recurrence during that period. The treatment success rate at 8 weeks was 83.0%. No significant differences were observed in treatment success rates among subgroups based on age (< 65 years old vs. ≥ 65 years old: 85.9% vs. 80.2%, p = 0.20), duration of the antibiotic washout period (24 h: 80.0%, 48 h: 84.5%, 72 h: 85.0%, p = 0.68), number of prior CDI recurrences (< 3 vs. ≥ 3: 82.5% vs. 83.1%, p = 0.60), or prior bezlotoxumab use (86.4% vs. 83.7%, p = 1.00). Patients receiving RBL at home had a higher treatment success rate compared to those receiving RBL in a clinic (87.3% vs. 62.5%, p < 0.01). Conclusions RBL was highly effective in preventing rCDI in a real-world setting, including at-home administration. The effectiveness was also observed among high-risk subgroups, such as patients ≥ 65 years old and those with ≥ 3 prior CDI recurrences.